Surgical Management of Lumbar intervertebral Disc hernaition - Ilyas, Muhammad; Shah, Azaz Ali; Khan, Muhammad Tariq (Journal of Postgraduate Medical Institute, 2011)
Two hundred patients of prolapsed intervertebral disc who were not responding to conservative treatment were selected for surgery. The age, sex signs and symptoms of the patietns were noted. All the patients were assessed clinicaly and confirmed with myelogram or CT scan of the affected levels of spine. There were120 male and 80 female patients. the disease is common between 20 - 40 years. Usually two levels 1 -4-5 and L5-S1 are affected more often than others. In two third of the patients the results were good to excellent. The best results were found to those patient of sciatica who presented initally with leg pain. Associated spinal stenosis with interverteb ral disc herniation is the important finding noted in one third of the patients. Decompression laminectomy with discectomy has the advantage that prolapsed disc can be removed bilaterally and simultaneously decompression of the canal can be carried out if it exists.